2015
DOI: 10.7567/jjap.54.06gd01
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity and growth regulation of Brassicaceae induced by oxygen radical irradiation

Abstract: The growth regulation characteristics of plants are investigated when plant seeds are irradiated with atmospheric discharge plasma. Enhancement of the germination and lengths of the stem and root of plants are observed after seeding. The total length of the stem and root increases approximately 1.6 times after a cultivation period of 72 h. The growth regulation effect is found to be maintained for 80 h of cultivation after seeding. The growth regulation originates from the change in the antioxidative activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…We suggest that if an alteration in the ABC mechanism took place in treatments, it must have been a slight one. In regard with thiols, Hayashi et al 16 observed that thioredoxin and glutathione production was involved in the promotion phenomenon induced by plasma, suggesting that the decrease in excess oxidative substances in a plant could boost its growth. Accordingly, we determined the quantity of GSH (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that if an alteration in the ABC mechanism took place in treatments, it must have been a slight one. In regard with thiols, Hayashi et al 16 observed that thioredoxin and glutathione production was involved in the promotion phenomenon induced by plasma, suggesting that the decrease in excess oxidative substances in a plant could boost its growth. Accordingly, we determined the quantity of GSH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al 16 proposed that plant growth promotion by plasma could be explained by the enhanced production of reduction-type thiols (thioredoxin and glutathione) and polyphenols, triggered by the produced ROS. Interestingly, these thiols are critical molecules in nodulation as well.…”
mentioning
confidence: 99%
“…The change of wetting properties and structure of the coat increases the water uptake, the permeability of nutrients, or it accelerates the root formation . Furthermore, several effects on plant hormones, enzymes such as catalase, proteins, soluble sugar, and antioxidants are possible . The plasma treatment is not only affecting the seeds, but it also affects the environmental conditions, such as the pH‐value or the introduction of nitrate and nitrous species into the surrounding water.…”
Section: Plasma Technology For and In Agriculturementioning
confidence: 99%
“…The plasma treatment is not only affecting the seeds, but it also affects the environmental conditions, such as the pH‐value or the introduction of nitrate and nitrous species into the surrounding water. All of these changes result in increasing the sprouting and germination rates, and faster initiation of germination . Finally, application of plasmas may also lead to an enhanced plant growth .…”
Section: Plasma Technology For and In Agriculturementioning
confidence: 99%
“…The study revealed that plasma was effective in changing the substantial in the vigor and rate of germination, resulting in an enhancing in germination. The facts lead to higher germination that plasma could change the antioxidative activity of plant cells through the action of oxygen species and/or active nitrogen species on the seed coat (Hayashi, Ono, Shiratani, & Yonesu, ). In addition, the application of plasma on solid foods is usually limited to surface processing.…”
Section: Introductionmentioning
confidence: 99%